Physiological determinants of performance in slalom paddling - Kearney, J. T.; McDowell, S.; Litschert, J.; Fleck, S. (Medicine & Science in Sports & Exercise, 1994)
Short summary: Although some relationships were identified between physiological factors and performance, variables other than those tested (30-sec upper body Wingate; 3 min post lactate; body composition; anthropometric profile; 10 m flat water sprint; grip strength; pulmonary function; post-race lactates) are major determinants of slalom paddling.